Consensus Based Economic Dispatch including System Power Losses - Tejaswini, K. Naga; Rao, G. Kesava (International Journal of Engineering and Technology, 2018)
Economic dispatch (ED) is an important class of optimization problem in Power System Operation. As both conventional and heuristic methods to solve EDP are centrally controlled, which may leads to some performance limitations, a Consensus based distributed algorithm is proposed in this paper to solve Economic Dispatch with inclusion of losses. Earlier, some papers dealt with the consensus based methods to solve Economic dispatch, but here in this paper the losses are included and the variation of losses at each iteration are also used to update the mismatch, which has some major prominence in the present day Power system environment. In this paper, the mismatch between load demand and total power generation is collectively learnt by the each generator, unlike the centralized approach, through the strongly connected communication network. MATLAB results in IEEE 6-bus system validate the potency and efficacy of the proposed technique